Does Certificate of Need Minimize Intensity Modulated Radiation Therapy Use in Patients with Low Risk Prostate Cancer?. Issue 5 (September 2016) - Kim, Sung; Patel, Akshar N.; Nelson, Carl; Shen, Shunhua; Mayer, Tina; Moore, Dirk F.; Lu‐Yao, Grace L.
Abstract : Introduction: : Certificate of need laws are optional from state to state, and are meant to limit the proliferation of certain unnecessary medical facilities. Theoretically, certificate of need laws should limit the use of intensity modulated radiation therapy in the population who likely would benefit from it the least, that is older or frail men with low risk prostate cancer. We evaluated the effect of certificate of need laws on the use of intensity modulated radiation therapy in these patients in a population based cohort. Methods: : Using the SEER (Surveillance, Epidemiology, and End Results) database linked with Medicare files we identified male residents of SEER regions who were diagnosed in 2004 to 2009 with low risk prostate cancer (T1, Gleason 6 or less, prostate specific antigen less than 10 ng/ml), who were 70 years old or older, or 65 years old or older, with a Charlson comorbidity score of 2 or greater. The end point was percentage of newly diagnosed patients who were treated with intensity modulated radiation therapy within 12 months of cancer diagnosis. Logistic regression was used to assess the impact of certificate of need laws on the use of intensity modulated radiation therapy. Results: : More than 37% (4, 491) of the patients came from states with radiation oncology certificate of need laws whereas 63% (7, 572) came from states without certificate of need laws. Intensity modulated radiation therapy was performed in 30% of certificate of need cases vs 28% of noncertificate of need cases. Logistic regression analysis revealed that intensity modulated radiation therapy was used more often in states with certificate of need laws than in states without certificate of need laws (OR 1.13, 95% CI 1.04–1.23, p=0.006). Conclusions: : Certificate of need laws do not effectively limit the use of intensity modulated radiation therapy in older or frail patients with low risk prostate cancer.